Comparison of Fulton’s Condition Factor of Nile Tilapia (Oreochromis niloticus L.) Reared in Ponds in Lubao, Pampanga, Philippines During the Dry Season - A.T., Reyes (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
This study has evaluated the condition factor of Nile tilapia (Oreochromis niloticus L.) that were reared in grow-out ponds in Lubao, Pampanga, Philippines during the 2018 dry season by using data of lengths and weights. The Fulton’s condition factor was computed by sex, life stage and physical health condition of the fish. From the 400 tilapia samples in 20 grow-out farms, 244 were males and 156 were females, 156 were juveniles and 244 were adults, and 251 were presumed healthy and 149 were presumed non-healthy. Juvenile tilapia (1.956±0.505) had a significantly lower condition factor compared to adults (2.232±0.498). Additionally, presumed healthy tilapia (2.235±0.536) had a significantly higher condition factor than presumed non-healthy (2.026±0.480). By farm level, the condition factor of male tilapia reared in farm 11 (2.792±0.765) was significantly higher as compared to farms 1 (2.043±0.333), 2 (1.997±0.255), 4 (2.049±0.326), 5 (1.994±0.144), 6 (2.084±0.225), 7 (1.782±0.526), 10 (2.098±0.308), 13 (1.716±0.425), 14 (1.804±0.289), 15 (1.960±0.531), 17 (2.028±0.352) and 20 (1.974±0.351). By female sex, statistical comparison of the condition factor of the 20 farms showed no significant difference. The condition factor values of juvenile tilapia in farms 3 (2.257±0.283), 11 (2.242±0.335) and 18 (2.250±0.914) were significantly higher as compared to farm 7 (1.271±0.703). By adult tilapia, the computed condition factor in farm 11 (2.976±0.791) was significantly higher compared to farms 1 (2.178±0.592), 2 (2.177±0.591), 5 (2.028±0.213), 7 (1.952±0.459), 8 (2.193±0.303), 10 (2.052±0.380), 15 (2.160±0.558) and 18 (2.094±0.189). The presumed healthy tilapia samples in the 20 farms had comparable values of condition factors; meanwhile, in the presumed non-healthy samples, the condition factor of farm 11 (2.455±0.819) was statistically higher compared to farm 13 (1.605±0.266). The probable factor that influenced the condition factors based on sex, life stage and physical health condition was water quality, specially dissolved oxygen, nitrite and phosphorus, since most of the 20 grow-out farms shared comparable cultural and management practices.